2012
DOI: 10.1292/jvms.11-0497
|View full text |Cite
|
Sign up to set email alerts
|

Assessment for Predicting Parturition in Mares Based on Prepartum Temperature Changes Using a Digital Rectal Thermometer and Microchip Transponder Thermometry Device

Abstract: ABSTRACT. The purpose of this study was to observe the changes in body temperature before parturition using a wireless temperature monitoring device (WTMD) and to evaluate the usefulness of body temperature measurements using a digital rectal thermometer (DRT) and a microchip transponder thermometry device (MTTD) for predicting parturition in mares. The body temperatures using a WTMD at 0 hr and −1 hr were significantly different from those at the same time on Days 1-5 (P<0.01). The temperature differences bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Korosue et al . [ 8 ] reported a specificity of 77% for days 1–5 before parturition and a sensitivity of 71% on the evening before parturition for internal body temperature measured using a microchip implanted in the neck. Auclair-Ronzaud et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Korosue et al . [ 8 ] reported a specificity of 77% for days 1–5 before parturition and a sensitivity of 71% on the evening before parturition for internal body temperature measured using a microchip implanted in the neck. Auclair-Ronzaud et al .…”
Section: Discussionmentioning
confidence: 99%
“…Korosue et al [8] reported a specificity of 77% for days 1-5 before parturition and a sensitivity of 71% on the evening before parturition for internal body temperature measured using a microchip implanted in the neck. Auclair-Ronzaud et al [9], using a microchip implanted in the neck, achieved a sensitivity of 96.9% and a specificity of 95% when comparing the average temperature of the 12 h before parturition to the temperatures from the preceding days at the same time of day.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cattle [7], sheep [8] and dogs [9], body temperature has been shown to be a relevant indicator of impending parturition. Several studies also reported that body temperature decreases just before foaling in mares [10][11][12]. However, examination of body temperature is not commonly used in the field for predicting time of foaling.…”
Section: Introductionmentioning
confidence: 99%